Mudala: A blockchain-based carbon credit exchange platform - Nyandu, Liso (School of Economics, 2025)
Climate change is one of the most pressing issues of our time, with constantly increasing greenhouse gas (GHG) emissions posing a severe threat to our planet. Businesses must adopt net-zero strategies such as reducing energy use, adopting carbon-neutral technologies, and trading on carbon markets to mitigate the effects of climate change. However, existing carbon markets, which are meant to incentivise emission reduction, face critical challenges such as a lack of trust and transparency, over-crediting, and high trading costs, hindering their effectiveness. We propose Mudala - a proof-of-concept carbon exchange built on the Algorand blockchain - to overcome these challenges. By leveraging blockchain technology's decentralised, immutable, and peer-to-peer transacting properties, Mudala enables firms to list carbon-offsetting projects, which, once approved by a regulator, are available for purchase as carbon credits by firms seeking to offset their emissions. The carbon credits exist as fungible tokens on a secure distributed ledger. Each firm authenticates using its unique Algorand account to access the web-based carbon exchange. The Paris Agreement highlights the urgent need for secure digital infrastructure to ensure data integrity and accurate emission tracking. The design of Mudala is undertaken within this context, and the resulting proof-of-concept demonstrates such secure digital infrastructure, which enhances trust, transparency, efficiency, and accessibility in carbon markets. To assess Mudala's effectiveness in addressing climate challenges, we employ a blockchain suitability workflow based on technical performance, data governance and access criteria. This analysis confirms the suitability of enabling Mudala's marketplace capability using blockchain. Our proof-of-concept successfully showcases secure digital infrastructure in carbon markets, aligned with the Paris Agreement's goals for data integrity and accurate emission tracking. While Mudala's features are promising, real world data on user engagement, project participation, and user feedback are crucial to fully validate its effectiveness and scalability